2012
DOI: 10.1113/expphysiol.2012.067249
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke induces endoplasmic reticulum stress response and proteasomal dysfunction in human alveolar epithelial cells

Abstract: New findings r What is the central question of this study?The endoplasmic reticulum stress response caused by cigarette smoke may lead to excessive apoptosis with disruption of the epithelial barrier, thus contributing to chronic obstructive pulmonary disease. One way of promoting cell survival is to facilitate degradation of cigarette smoke-induced protein damage through the ubiquitin-proteasome pathway. Direct effects of gas-phase cigarette smoke on proteasomal activities have not been demonstrated previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 43 publications
5
51
2
Order By: Relevance
“…The mechanisms underlying CS-induced epithelial cell injury and dysfunction remain unclear, but may include a protease/antiprotease imbalance, inflammation, oxidative stress, and programmed cell death (2)(3)(4). Recent studies have suggested additional pathway mechanisms involving altered protein homeostasis (proteostasis) (5,6), including ER stress, inhibition of the ubiquitin-proteasome system (7)(8)(9), and autophagy (10)(11)(12)(13), all of which potentially contribute to the pathogenesis of chronic lung diseases and emphysema (5).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying CS-induced epithelial cell injury and dysfunction remain unclear, but may include a protease/antiprotease imbalance, inflammation, oxidative stress, and programmed cell death (2)(3)(4). Recent studies have suggested additional pathway mechanisms involving altered protein homeostasis (proteostasis) (5,6), including ER stress, inhibition of the ubiquitin-proteasome system (7)(8)(9), and autophagy (10)(11)(12)(13), all of which potentially contribute to the pathogenesis of chronic lung diseases and emphysema (5).…”
Section: Introductionmentioning
confidence: 99%
“…One plausible explanation is that recovery of protein synthesis is pro-survival during responses to transient ER stress, but becomes toxic during chronic ER stress, when ongoing protein synthesis overwhelms the adaptive potential of the system. Evidence has implicated these pathways in the responses to oxidative stress imposed by cigarette smoke, but this requires further exploration [25][26][27][28]. Although ATF4 signalling is activated in the airways of many patients with chronic obstructive pulmonary disease [44], a direct mechanistic link with disease pathogenesis remains elusive.…”
Section: Upr Sensorsmentioning
confidence: 99%
“…CS exposure may impair the delivery of bacteria to lysosomes (115), suggesting that defective xenophagy in alveolar macrophages of smokers may contribute to recurrent infections in COPD patients. CS affects oxidative protein folding in the ER (74), and it can induce the UPR in human alveolar epithelial cells (165), which may lead to ER stress and impaired protein homeostasis in the lungs of COPD patients (13,105,111).…”
Section: Figmentioning
confidence: 99%